Process analysis of a furniture micro-enterprise by conceptual modeling and dynamic simulation (Research, Society and Development, 2020)
This article aims to evaluate the current layout of a furniture make-to-order shop floor in Itabira-MG. The chosen process was the manufacturing of Medium-Density Fiberboard (MDF) tables. The analysis is done through conceptual modeling called IDEF-SIM and dynamic simulation through the software FlexSim. The results prove the intense use of labor that is frequent in make-to-order production companies of the sector and suggests new studies of physical arrangement to optimize the productivity of the company.